KINEMATICS OF THE V MECHANISM USED FORELECTRIC SWITCHERS BASED ON SPECIALISED SOFTWARE - PĂUN ANTONESCU (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2015)
This paper is representing a continuing research of the doctoral thesis "Geometrical analysis and synthesis of mechanisms in the electrotechnical field". Using two Mathcad programs as mathematics analysis software and Solidworks as graphical analysis software it is dimensioned the new kinematics scheme of the high voltage V mechanism. Kinematic analysis is based on the mathematical model presented in the doctoral thesis mentioned above and graphical modeling and analysis is conducted to compare and complete the research regarding the V mechanism triadic chain 5R + T type.